2023
DOI: 10.1109/tap.2022.3216555
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Programmable Scattering for Wireless Coverage Enhancement: An Indoor Field Trial Campaign

Abstract: This paper presents a multi-bit reconfigurable intelligent surface (RIS) with a high phase resolution, capable of beam-steering in the azimuthal plane at sub-6 Gigahertz (GHz). Field trials in realistic indoor deployments have been carried out, with coverage enhancement performance ascertained for three common wireless communication scenarios. Namely, serving users in an open lobby with mixed line of sight and nonline of sight conditions, communication via a junction between long corridors, and a multi-floor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 34 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…37 (a), Fig. A multi-bit PIN diode-based RIS capable of beam steering at the sub-6 GHz was proposed in [141]. An indoor field trial was carried out for different scenarios.…”
Section: G 275-bit 3-bit Coding Multi-bit Reconfigurable Intelligent ...mentioning
confidence: 99%
“…37 (a), Fig. A multi-bit PIN diode-based RIS capable of beam steering at the sub-6 GHz was proposed in [141]. An indoor field trial was carried out for different scenarios.…”
Section: G 275-bit 3-bit Coding Multi-bit Reconfigurable Intelligent ...mentioning
confidence: 99%
“…Compared to the previous references (Trichopoulos et al, 2022)- (Araghi et al, 2022), the proposed unit cell has a higher loss than the 1-bit unit cell presented from (Trichopoulos et al, 2022) and the 2-bit unit cell from (Dai et al, 2020), although both unit cells operate at lower frequencies. The 1-bit unit cell at 28.5 GHz from (Gros et al, 2021) showed a maximum reflection amplitude of -3 dB using PIN diodes, whereas the one from (Rains et al, 2021) can generate a 3-bit phase response with −4.65 dB maximum reflection amplitude at 3.75 GHz. The unit cells from (Pei et al, 2021) and (Araghi et al, 2022) used varactor diodes as tuning elements at 5.8 and 3.5 GHz, respectively.…”
Section: Unit Cell Designmentioning
confidence: 99%
“…Since then, many works have been published in RIS based on PCB solutions with PIN and varactor diodes as tuning elements and patch reflectors (Trichopoulos et al, 2022)- (Araghi et al, 2022). To generate the unit cell reflection phase tunability, patch elements might be connected to parasitic elements (Trichopoulos et al, 2022), (Gros et al, 2021), grounded elements (Pei et al, 2021), (Rains et al, 2021), or between them (Araghi et al, 2022). Also, a different approach was proposed in (Dai et al, 2020) based on a top patch element interaction with a slotloaded plane between it and the ground plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since P dynamic ≈ 0, varactor-diode-based RIS has potential of achieving low power consumption compared with PIN-diode-based RIS. However, it should be noted that the control circuit of varactor-diode based RIS is often much more complicated, i.e., a varactor diode interfaced with voltage level shifter circuity or DACs, whereas PIN-diode based RIS only needs shift register and FPGA [12]. In addition, most of RISs working in high frequency (i.e., mmWave band) belong to the…”
Section: Preliminary Power Consumption Modelingmentioning
confidence: 99%